Extracts of Thai Perilla frutescens nutlets attenuate tumour necrosis factor-α-activated generation of microparticles, ICAM-1 and IL-6 in human endothelial cells - Narisara Paradee (2020)
© 2020 The Author(s). Elevation of endothelial microparticles (EMPs) play an important role in the progression of inflammation-related vascular diseases such as cardiovascular diseases (CVDs). Thai perilla (Perilla frutescens) nutlets are rich in phenolic compounds and flavonoids that exert potent antioxidant and anti-inflammatory effects. We found that the ethyl acetate (EA) and ethanol (Eth) extracts of Thai perilla nutlets contain phenolic compounds such as luteolin, apigenin, chryseoriol and their glycosides, which exhibit antioxidant activity. The goal of the present study was to investigate the effects of the extracts on endothelial activation and EMPs generation in tumour necrosis factor-α (TNF-α)-induced EA.hy926 cells. We found that TNF-α (10 ng/ml) activated EA.hy926 cells and subsequently generated EMPs. Pre-treatment with the extracts significantly attenuated endothelial activation by decreasing the expression of the intracellular adhesion molecule-1 (ICAM-1) in a dose-dependent manner. Only the Eth extract showed protective effects against overproduction of interleukin-6 (IL-6) in the activated cells. Furthermore, the extracts significantly reduced TNF-α-enhanced EMPs generation in a dose-dependent manner. In conclusion, Thai perilla nutlet extracts, especially the Eth extract, may have potential to protect endothelium against vascular inflammation through the inhibition of endothelial activation and the generation of endothelial microparticles (EMPs).